The reliability of medial and lateral plantar nerve recordings in healthy elderly individuals - ULUÇ, KAYIHAN; KAHRAMAN KOYTAK, PINAR; TANRIDAĞ, TÜLİN (SPRINGER-VERLAG ITALIA SRL, 2015)
The aim of this study was to investigate the reliability of medial plantar (MP) and lateral plantar (LP) nerve conduction studies (NCS) in healthy individuals aged > 65 years, and to obtain reference values for this age group. The study included 81 healthy subjects. MP response was absent in only 2 subjects, but LP response could not be obtained bilaterally in 43 of the 81 subjects. Regression analysis showed that MP NCS could be reliably performed in those aged a parts per thousand currency sign72 years and normal values for MP nerve in individuals aged 66-72 years would be strongly against a large-fiber neuropathy. However, LP response was absent in 53.1 % of the healthy elderly subjects; therefore, we think it is unreliable to study the LP nerve in this age group.
Keywords: Medial plantar nerve; Lateral plantar nerve; Nerve conduction study; The elderly; SENSORY NEUROPATHY; SURAL NERVES; CONDUCTION; AGE; SIZE